Examining the Relationship between Social Determinants of Health and Adverse Pregnancy Outcomes in Black Women - Walker, Shannon L.; Walker, Rebekah J.; Palatnik, Anna; Dawson, Aprill Z.; Williams, Joni S.; Egede, Leonard E. (American Journal of Perinatology, 2023)
Objective Our objective was to examine associations between social determinants of health (cultural, neighborhood, and psychosocial factors) and adverse pregnancy outcomes (gestational age at birth [GAB], preterm birth [PTB], and preeclampsia) in Black women.Study Design Cross-sectional data (n = 204) comprised adult Black women aged ≥18 years who delivered between 2013 and 2022 in Milwaukee,Wisconsin. Sequential unadjusted linear and logistic regression models were run to evaluate associations between social determinants of health and pregnancy outcomes. Stepwise regressions with forward selection were run to test the contribution of the social determinants of health to adverse pregnancy outcomes, independent of the contribution of established risk factors.Results Mean GAB was 37.9 weeks, 19.6% had a PTB and 17.7% had preeclampsia. In all fully adjusted models, education (β0.15, 95% confidence interval [CI]: 0.005, 0.29), nulliparity (β −1.26, 95%CI: −2.08, −0.44), multifetal gestation (β −2.67, 95% CI: −4.29, −1.05), and exposure to neighborhood violence (β −0.13, 95%CI: −0.25, −0.005) were associated with shortened GAB. Education (adjusted odds ratio [aOR]: 0.83, 95%CI: 0.69, 0.99), provider trust (aOR: 0.94, 95%CI: 0.88, 0.99), chance health locus of control (aOR: 0.88, 95%CI: 0.78, 0.99), and anxiety (aOR: 0.81, 95%CI: 0.69, 0.95) were associated with reduced odds of PTB. Powerful others health locus of control (aOR: 1.16, 95%CI: 1.03, 1.32), depression (aOR: 1.17, 95%CI: 1.01, 1.34), nulliparity (aOR: 4.73, 95%CI: 1.79, 12.55), multifetal gestation (aOR: 17.78, 95%CI: 3.49, 90.50), diabetes (aOR: 4.71, 95%CI: 1.17, 19.00), and obstructive sleep apnea (aOR: 44.28, 95%CI: 2.50, 783.12) were associated with increased odds of PTB. Internal health locus of control (aOR: 1.13, 95%CI: 1.01, 1.25), depression (aOR: 1.09, 95%CI: 1.01, 1.17), preeclampsia in a previous pregnancy (aOR: 5.96, 95% CI: 2.22, 16.01), and kidney disease (aOR: 34.27, 95% CI: 1.54, 763.75) were associated with preeclampsia.Conclusion Provider trust, health locus of control, neighborhood violence, depression, and anxiety were associated with adverse pregnancy outcomes in Black women, independent of demographic and clinical risk factors.Key Points
Keywords: social determinants of health; preterm birth; preeclampsia; race/ethnicity; health disparities